2020
DOI: 10.1111/cas.14764
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant overexpression of mir‐182‐5p and mir‐182‐3p raises the possibility of IL‐17–producing Treg formation in breast cancer by targeting CD3d, ITK, FOXO1, and NFATs: A meta‐analysis and experimental study

Abstract: T cells are polarized toward regulatory T cells (Tregs) in tumor microenvironment by the shuttling of microRNAs that target T cell–activating signaling pathways. We evaluated the expression of the miR‐182 cluster (miR‐96, 182, and 183) in peripheral blood mononuclear cells (PBMCs) of patients with breast cancer (BC), and T cell polarization by the expression of FOXO1, NFATs, ITK, TCR/CD3 complex, and IL‐2/IL‐2RA. Twenty‐six microRNAs overexpressed in tumor tissues and sera of these patients were extracted by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 49 publications
0
66
0
1
Order By: Relevance
“…Previous study has showed that CD3D is closely related to glioblastoma multiforme [ 38 ], cervical cancer [ 39 ], and breast cancer [ 40 ]. Another study showed that CD3D was the target of mir-182-5p and might be used as candidate biomarkers of breast cancer [ 41 ]. However, there is still a lack of comprehensive analyses of CD3D in MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has showed that CD3D is closely related to glioblastoma multiforme [ 38 ], cervical cancer [ 39 ], and breast cancer [ 40 ]. Another study showed that CD3D was the target of mir-182-5p and might be used as candidate biomarkers of breast cancer [ 41 ]. However, there is still a lack of comprehensive analyses of CD3D in MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Transduced cells were subsequently exposed to 2.5 μg/mL puromycin (Sigma, St. Louis, MO, USA) for two days to obtain stable transductants. 25 …”
Section: Methodsmentioning
confidence: 99%
“…According to ALD mouse and cell models, we found that FOXO1 was significantly repressed by alcohol consumption, thus further confirming its importance in ALD development. We used dual-luciferase reporter assays to explore the regulatory mechanism, which showed that miR-182-5p targets the 3′UTR binding site of FOXO1 as also demonstrated in Soheilifar's study ( 32 ). RT-PCR and western blotting revealed that over-expression of miR-182-5p dramatically decreased the expression of FOXO1 mRNA and protein.…”
Section: Discussionmentioning
confidence: 73%